How to Build an Entrepreneurial Spirit from an Early Age for Senior High School Students of Gurukula Bangli - Permana, Dewa Gde Yoga; Dewi, Gita Apsari; Werthi, Komang Tri; Perwira, A. A. Gde Agung Nanda; Putra, I Made Luhur Adi (CV Media Inti Teknologi, 2025)
The purpose of this activity is to provide a basic understanding of the concept of entrepreneurship and business development and to inspire students to start recognizing business opportunities around them. Amidst the development of technology and globalization, the world of work is undergoing major changes. The trend of digitalization has created great opportunities for the younger generation to start businesses based on creativity and technology. High school students are at an age where creativity is developing rapidly. They have great potential to recognize opportunities around them, especially in local contexts such as the food sector, crafts, and technology-based services. The method used in this activity began with field observations by visiting students at Gurukula Bangli Senior High School. It continued with a presentation from the lecturer on the problems faced by the students, then a discussion related to the presentation material presented. There was an increase in scores from the pre-test to the post-test of 41.79% of all Gurukula Bangli high school students who participated in community service. The assessment results show that students can understand good business opportunities that have great potential for students and are brave enough to start small steps in the business world. The author appeals that there is still a need for real action from students to see these business opportunities as an opportunity that must be utilized to achieve success.